2021
DOI: 10.1002/adfm.202101966
|View full text |Cite
|
Sign up to set email alerts
|

Amplifying Surface Energy Difference toward Anisotropic Growth of All‐Inorganic Perovskite Single‐Crystal Wires for Highly Sensitive Photodetector

Abstract: It is a great challenge to directly grow super long all‐inorganic perovskite monocrystalline wires due to the weak surface energy difference among the low index facets. Here, a one‐pot solution process to grow the aspect ratio over 105 of monocrystalline CsPbBr3 perovskite wires (PWs) and yield up to 70% is reported. A chemical potential dependent surface energy difference amplification strategy is proposed to regulate the surface energy of growing and grown surfaces accordingly to the anisotropic growth of Cs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 61 publications
(24 reference statements)
2
26
0
Order By: Relevance
“…Chen et al also reported an increased difference in surface energies between (110) and (001) planes for growing CsPbBr 3 nanowires. 17 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al also reported an increased difference in surface energies between (110) and (001) planes for growing CsPbBr 3 nanowires. 17 …”
Section: Resultsmentioning
confidence: 99%
“…Chen et al also reported an increased difference in surface energies between (110) and (001) planes for growing CsPbBr 3 nanowires. 17 According to the above analysis, the proposed growth mechanism is shown schematically in Figure 3g: The nanowires first nucleate inside the pores, since the AAO nanopores have ample surface area for heterogeneous nucleation. 21 The nanowires preferentially nucleate with the (001) planes orthogonal to the pores, that is, with the (110) side facets parallel to the AAO pore walls, presumably because (110) has the lowest solid−solid interfacial energy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is easy to understand because a higher concentration of precursors can enable a more sufficient growth of products and a larger diameter of MWs. In our case, the growth of Rb 2 CuBr 3 MWs is very similar to that of CsPbBr 3 perovskite wires, 47 and the mechanism can be interpreted in this way: Owing to the 1D chain structure of orthorhombic Rb 2 CuBr 3 , it tends to grow into a wire morphology. Although a large concentration of liquid precursors increases the growth rate of microwires in the direction perpendicular to the wire, it is still much lower than the growth rate along the wire.…”
Section: ■ Results and Discussionmentioning
confidence: 99%